Research on Flood Impact and River Regime of Skew Bridges Crossing River Bend Based on FVM Method - NIU Jiao; CHENG Jingqing; YAN Xiaoyu; JIA Lei; WANG Zhichao (Renmin Zhujiang)
Based on finite volume method (FVM) and two-dimension unstructured grid,taking a skew bridge crossing the river bend as the research object,this paper builds a hydrodynamic model of the upstream and downstream of the bridge,and simulates and analyzes the impact of bridge construction on the upstream and downstream water level,flow velocity and river regime under different frequency floods.The results show that:Due to the water blocking action of the piers,the upstream water level of the bridge increases,the flow velocity between the piers increases,and the flow velocity of water face and back face of the piers decreases.As there is a angle between piers of the skew bridge and the natural river course,the water level on the left bank in the downstream rises and the right bank in the downstream drops.The flow velocity and sediment-carrying capacity on the left bank increases compared to those before the project,while those on the right bank decreases,and the affected area was concentrated in the river section near the bridge location.The river section where the bridge is located is bent.The bridge can play a positive role in preventing the siltation of convex bank (left bank) and the scour of concave bank (right bank) downstream the bridge.The research results can provide reference for the design of skew bridge.